2017
DOI: 10.1177/1350650117696388
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes and superplasticizer reinforcing cementitious composite for aerostatic porous bearing

Abstract: Cementitious composites are low cost and readily manufactured materials which can be used for specialist applications such as the production of aerostatic porous bearings. A design of experiment was used to identify the effects of superplasticizer additions and carbon nanotube inclusions on the physical and mechanical properties of cementitious composites which can be applied as porous restrictor in aerostatic thrust bearings. The presence of carbon nanotubes was able to increase the bulk density, the compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Finally, from both sides of the gas film flow into the compression and discharge chambers of the linear compressor respectively. Therefore, the flow of gas in the bearing is divided into two main parts, one is the flow of gas in the porous media material and the other is the flow of gas in the bearing gap [13][14][15][16][17][18] . The gas in porous materials is mainly viscous flow, when the viscous gas flows through the porous material with a certain pressure difference, the gas motion must satisfy Darcy's law, that is, the relationship between the gas velocity and the gas pressure gradient in all directions of the porous medium is [19][20][21][22] :…”
Section: Working Principle and Mathematical Modeling Of Porous Gas Be...mentioning
confidence: 99%
“…Finally, from both sides of the gas film flow into the compression and discharge chambers of the linear compressor respectively. Therefore, the flow of gas in the bearing is divided into two main parts, one is the flow of gas in the porous media material and the other is the flow of gas in the bearing gap [13][14][15][16][17][18] . The gas in porous materials is mainly viscous flow, when the viscous gas flows through the porous material with a certain pressure difference, the gas motion must satisfy Darcy's law, that is, the relationship between the gas velocity and the gas pressure gradient in all directions of the porous medium is [19][20][21][22] :…”
Section: Working Principle and Mathematical Modeling Of Porous Gas Be...mentioning
confidence: 99%
“…Hosokawa et al [16] found that LCC of aerostatic thrust bearings with partial porous material restrictor decreased while stiffness improved compared to the bearing with traditional porous material restrictor. Silva et al [17] used compound materials made of 0.4 wt.% of superplasticizer and 0.05 wt.% of carbon nanotubes as double-layered porous material restrictor in aerostatic thrust bearings and achieved acceptable bearing performance. Zheng et al [18] experimentally verified that aerostatic thrust bearing compensated by a restrictor with multi-orifice series has higher maximal stiffness compared to the bearing with traditional orifice type restrictor.…”
Section: Introductionmentioning
confidence: 99%
“…The first thought with regarding to the instability of PAJBs is air hammer because it belongs to the aerostatic bearings. Many studies [4][5][6][7][8][9] have been conducted to research the air hammer instability of PAJBs. These studies were mainly concerned about the influences of permeability and porosity, which are special parameters of the porous material.…”
mentioning
confidence: 99%